Preventing teen pregnancy and delinquency: The role of parental supervision, communication, and education - Utami, Fitriana Putri; Nurfita, Desi; Syam, Nur Syarianingsih; Ramadhani, Khairunisa; Matahari, Ratu (Jurnal Cakrawala Promkes, 2024)
Adolescent pregnancies resulting from premarital sex impacted adolescents, their families, and any potential offspring. Society viewed such pregnancies sas abnormal, careless, and embarrassing. Given that adolescents are still under the of the influence of  their families, parental roles were crucial in preventing these pregnancies, despite adolescents increasingly choosing their own friends . In the contemporary digital age, gadget addiction further complicates family dynamics, particularly in managing adolescent behavior. Thus, this study aims to investigate how parents supervise, communicate, and educate their adolescents to prevent teenage pregnancies and other juvenile delinquency. Conducted in Banguntapan District, Bantul Regency, Yogyakarta, in February 2024, this qualitative study involved six women from the Youth Family Development program in Mertosanan Kulon as primary informants and the head of Mertosanan Hamlet as a triangulating informant. All informants were selected using a purposive technique.  Data collection was conducted through Focus Group Discussion (FGD)and analyzed using content analysis. Parents can contribute in preventing juvenile misbehavior, particularly when it comes to preventing unmarried pregnancies, by keeping an eye on, talking to, and educating their teenagers—. Fathers play a more crucial role in the upbringing and educatiing boys, while mothers are more critical for girls. Collaborative community efforts and a multidisciplinary educational approach emphasizing parent-adolescent relationships and communication are essential.